PREDICTING THE BEHAVIORAL INTENTION TO USE MOBILE PAYMENT IN AN EMERGING COUNTRY: THE ROLE OF TRUST AS A MEDIATING VARIABLE - Hanif Adinugroho Widyanto; Kunthi Afrilinda Kusumawardani (Proceeding of the International Conference on Family Business and Entrepreneurship, 2021)
The objective of this research was to analyze the predicting factors of Behavioral Intention to use a mobile payment service in an emerging country, namely Performance Expectancy, Effort Expectancy, Social Influence, Trust, and Perceived Security. The respondents in this study were limited to the users of LinkAja, one of the largest Indonesian mobile payment services, who lived in the Greater Jakarta (Jabodetabek) area. The data collected in this research (n=144) were examined using a quantitative method with structural equation modeling analysis using partial least squares (PLS-SEM) technique. In the end, there were seven out of ten hypotheses in the present study which was supported by the data. The results of this study also exhibited the strategic importance of trust as a mediating construct in this study. The adjusted coefficient of determination for Behavioral Intention was 67.7%, suggesting a moderate-to-substantial in-sample predictive power. This research also offered a few managerial implications for LinkAja and the mobile payment industry in Indonesia. Keyword: Mobile Payment, Behavioral Intention, Performance Expectancy, Effort Expectancy, Social Influence